2009
DOI: 10.1158/0008-5472.can-09-0834
|View full text |Cite
|
Sign up to set email alerts
|

Immunoselection of Breast and Ovarian Cancer Cells with Trastuzumab and Natural Killer Cells: Selective Escape of CD44high/CD24low/HER2low Breast Cancer Stem Cells

Abstract: Although trastuzumab (Herceptin) has substantially improved the overall survival of patients with mammary carcinomas, even initially well-responding tumors often become resistant. Because natural killer (NK) cell-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) is thought to contribute to the therapeutic effects of trastuzumab, we have established a cell culture system to select for ADCC-resistant SK-OV-3 ovarian cancer and MCF7 mammary carcinoma cells. Ovarian cancer cells down-regulated HER2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 46 publications
5
88
1
Order By: Relevance
“…Most current anti-cancer therapeutics primarily target either differentiated or proliferating cancer cells, and, conceivably, will not be effective against undifferentiated cells that are mostly quiescent. Indeed, multiple lines of evidence have demonstrated that CSCs are more resistant to chemotherapeutics, radiation, and immunotherapy [124,144,145] and are endowed with enhanced ability to metastasize [146]. Moreover, many anti-cancer therapies may enrich CSCs [124,147], perhaps partially by inducing dedifferentiation ( Figure 5D).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Most current anti-cancer therapeutics primarily target either differentiated or proliferating cancer cells, and, conceivably, will not be effective against undifferentiated cells that are mostly quiescent. Indeed, multiple lines of evidence have demonstrated that CSCs are more resistant to chemotherapeutics, radiation, and immunotherapy [124,144,145] and are endowed with enhanced ability to metastasize [146]. Moreover, many anti-cancer therapies may enrich CSCs [124,147], perhaps partially by inducing dedifferentiation ( Figure 5D).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…The CD29 hi CD24 med cancer stem cells in tumors developed in WAPCre c Brca1 D11 p53 D5&6 mice expanded in cisplatin-refractory tumors (Shafee et al 2008). In several breast cancer cell lines, expansion of CD44 hi CD24 med cells was associated with herceptin resistance (Reim et al 2009). Strategies to target specific pathways required for the maintenance of cancer stem cells are being developed.…”
Section: Targeting Aberrant Pathways In Breast Cancersmentioning
confidence: 99%
“…These variant isoforms are expressed in many different organs and have been strongly linked to tumor progression behaviors in various cancers [41][42][43]. Expression of CD44 is widely identified in cancer stem cells in various organs, such as breast, colon, and pancreas [44][45][46]. Among these SCLC markers, CD133 and CD44, already validated as informative markers of stem cells in both primary tumors and xenografts, [24,25] have been identified in gene expression signatures whose genes have been shown to enhance cell migration and invasion activity from colon cancer to liver metastasis [47].…”
Section: Metastasismentioning
confidence: 99%